2013
DOI: 10.1134/s0006297913110035
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma and melanocortin 1 receptor

Abstract: The conventional chemotherapeutic treatment of malignant melanoma still remains poorly efficient in most cases. Thus the use of specific features of these tumors for development of new therapeutic modalities is highly needed. Melanocortin receptor-1 (MC1R) overexpression on the cell surface of the vast majority of human melanomas, making MC1R a valuable marker of these tumors, is one of these features. Naturally, MC1R plays a key role in skin protection against damaging ultraviolet radiation by regulating eume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 120 publications
0
51
0
3
Order By: Relevance
“…, 0 – 250 nM) over a 4 hour incubation period. Saturation binding was seen to occur at ~100 nM for the B16F10 cell line and 150 nM for M21 cells, which is likely related to known differences in the regulation of MC1-R expression in mouse and human cells, 46 a combination of receptor density, 14, 47 internalization kinetics, and receptor recycling rates. Furthermore, αMSH-PEG-C′ dot uptake in B16F10 and M21 cells using 100 nM concentrations was seen to increase as a function of incubation time by flow cytometry (Figure 3b), noting that maximum values for both cell types were found at 4–5 hours.…”
Section: Resultsmentioning
confidence: 91%
“…, 0 – 250 nM) over a 4 hour incubation period. Saturation binding was seen to occur at ~100 nM for the B16F10 cell line and 150 nM for M21 cells, which is likely related to known differences in the regulation of MC1-R expression in mouse and human cells, 46 a combination of receptor density, 14, 47 internalization kinetics, and receptor recycling rates. Furthermore, αMSH-PEG-C′ dot uptake in B16F10 and M21 cells using 100 nM concentrations was seen to increase as a function of incubation time by flow cytometry (Figure 3b), noting that maximum values for both cell types were found at 4–5 hours.…”
Section: Resultsmentioning
confidence: 91%
“…9,36 Potentially germane to the current studies with 111 In-NOTA-MNT-EGF, Chen et al 37 reported significant growth inhibition of In-MNT-EGF construct in the present article; however, we do note that in a previous study using residualizing 125 I labeling, the in vitro cytotoxicity of [ For in vivo proof-of-principle experiments, we selected MNT-MSH, targeted to melanoma cells, which overexpress MC1R. 38 This MNT has been regarded recently as a promising approach for the treatment of malignant melanoma, [39][40][41] including uveal melanoma. 42 Although skin melanomas are usually managed by surgical excision, ocular melanomas are routinely treated with brachytherapy.…”
mentioning
confidence: 42%
“…These high affinity ligands might also be used to deliver therapeutics selectively to melanoma cells. However, this targeting strategy has been criticized because stimulation of the MC1R has been shown to increase melanocyte proliferation, and potentially could lead to melanoma growth [227, 229]. The use of multivalent melanocortin ligands as diagnostic tools has been reviewed previously [224-228].…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%